Strategi Komunikasi Pemasaran Terpadu Digital Pada Proses Penerimaan Mahasiswa Baru Untar - Harlyan Octora; Silvanus Alvin (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
Tarumanagara University (UNTAR) always carries out the process of marketing activities in order to get new students every year. When the COVID-19 pandemic hit in March 2020, marketing activities that originally focused on offline activities had to be carried out online. This research is included as a qualitative research with a case study approach. Data collection was carried out in two ways, namely conducting in-depth interviews with UNTAR's marketing division and digging up secondary data in the form of archives or documents both physically and non-physically. This study reveals that UNTAR focuses its marketing communication strategy on the digital side, by focusing on advertising, interactive internet marketing, and sales promotion.